Benzoin 4-ethylthiosemicarbazone - Dinçer, M; Özdemir, N; Çukurovali, A; Yilmaz, I; Büyükgüngör, O (Int Union Crystallography, 2006)
In the title compound, 2-hydroxy-1,2-diphenylethanone 4-ethylthiosemicarbazone, C17H19N3OS, the thiosemicarbazone moiety is planar and has an E configuration. The planar phenyl rings make dihedral angles of 82.34 (8) and 8.07 (17)degrees with the plane of the thiosemicarbazone moiety. The crystal structure contains two intramolecular (N-H (...) O and N-H (...) N) and one intermolecular interaction (O-H (...) S), as well as two C-H (...) pi(benzene) interactions. Molecules are stacked in columns running along the a axis. Molecules in each column are connected to each other by means of linear O-H (...) S hydrogen bonds and C-H (...) pi interactions. In addition, there are also C-H (...) pi(benzene) interactions between the columns.
Keywords: Crystal-Structure; Molecular-Structures; Thiosemicarbazones; Reductase; Agents